Preliminary System Dynamics Model to Understand the Struggle of Downstream Agro-Industry Development in Aceh, Indonesia - Mulyati, Trisna; Prasetyo, Diaz Adi (INDEF - Institute for Development of Economics and Finance, 2023)
The successful agriculture industrialisation in developing regions is a big challenge which continues to be pursued globally. It is a dynamically complex system with many interplay stakeholders. Properly managing it therefore requires root understanding of the underlying structures and feedback mechanisms that influence the systems behaviour. This study explores the system dynamics modelling approach in Aceh that has been envisioning a progressive downstream agro-industry development for decades after the Tsunami and conflict rehabilitation but with very little success. The findings indicate that the reinforcing loop of numerous efforts is slow and worsened by the strong balancing loop of pressure from agriculture mafia in the system. This particularly includes the massive investment promotion that has caused a shifting of the burden for Aceh due to widespread extortion practice being unaddressed, and thus leading to temporary business establishments or inactive business plans. It is also evident that necessary law enforcement has been mainly ignored. Results from the simulation model have been able to replicate the historical behaviour of stagnant agribusiness growth in the downstream. Three scenarios were simulated in order to recommend policy intervention, which is by looking at the effect of doubled and halved extortion rate. The latter is projected to achieve a more favourable result for Aceh agro-industry development. In order to maintain the balance between economic growth, sustainable use of resources, and minimisation of unintended environmental and social consequences, such intervention is subjected to other policies. Keywords: agriculture, agro-industry, industrial development, system dynamics JEL: C63, O13, Q13